The Baltic challenge and Euro-area entry - Zsolt Darvas (Bruegel, 2009)
Resident Fellow Zsolt Darvas takes a look at the issue of the Baltic states - Estonia, Latvia and Lithuania - and the challenges facing those three countries in the aftermath of the financial crisis. He argues that because it is in the broader European interest to prevent a collapse in the Baltics, the best option is immediate euro entry at a suitable exchange rate supported by appropriate resolution in order to manage the resulting debt overhang. However, there seems to be no legal basis for this under the current euro accession criteria. Furthermore, the economic foundations of the criteria are fundamentally flawed, as euro-area members continue to violate the criteria while the EU's expansion to 27 members has made the criteria tougher for new member states to meet themselves. Ultimately, the European Council has the ability to reform the criteria without a formal treaty change. The Council should do so, the author argues, and allow for more meaningful benchmarks for all future euro-area applicants.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Eurozone; Wirtschaftslage; Wirtschaftspolitik; Geldpolitik; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Estland; Lettland; Litauen